Melampaui Sinologi Tradisional - Soebagjo, Natalia (Paradigma: Jurnal Kajian Budaya, 2012)
Indonesia has had a long history of interaction with China marked with periods of warm understanding and cold misunderstandings. In the modern era in particular ties have been complicated by domestic politics. As China rises in the 21st century and takes its place in the world, Indonesia has to be able to define its relationship vis-a-vis China. To be able to do this, Indonesians need to better understand China. Ability to understand the Chinese language and China’s culture, although basic and essential, is no longer enough. The study of modern China needs to go beyond the traditional understanding of Sinology, strengthened by other academic disciplines, if Indonesians want to better anticipate the dynamics of Indonesia-China relations. artefacts only but also from the existence of some vocabularies in the written and oral language in Indonesian language (Bahasa Indonesia). Survey concerned with the vocabularies in Indonesian language which derived from foreign language, including those words derived from Chinese language, was conducted by Russell Jones. The result had been written in a book called ‘Loan Words in Indonesian and Malay’. The survey had recorded around 1.100 words in Chinese language which had been borrowed by the Indonesian language and had spread out in differnt kinds of aspect of meaning, including the aspect of meaning related to food and beverage, which will be described in this paper. with Indonesian in the more penetrating globalization process in Asia in the 21st century. The research aims to examine the binding of two cultures tied in the knot in the marriage institution, its problem and negotiation. The qualitative methods used here is conducted through questionnaire and direct interview and through the social media. The result of which shows that factors such as cultural difference, respective country rules, and family tie interfere the social interaction in mixed marriage. But, despite the challenges, it is capable to generate negotiation and cultural appropriation of each party to support a multicultural and cosmopolitan marriage.